2010
DOI: 10.1074/jbc.m110.128371
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Prostate Cancer Cell Survival by Protein Kinase C∈ Involves Bad Phosphorylation and Modulation of the TNFα/JNK Pathway

Abstract: Protein kinase C⑀ (PKC⑀), a diacyglycerol-and phorbol esterresponsive serine-threonine kinase, has been implicated in mitogenic and survival control, and it is markedly overexpressed in human tumors, including in prostate cancer. Although prostate cancer cells undergo apoptosis in response to phorbol ester stimulation via PKC␦-mediated release of death factors, the involvement of PKC⑀ in this response is not known. PKC⑀ depletion by RNAi Protein kinase C (PKC), 3 a family of serine-threonine kinases that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 44 publications
3
41
0
Order By: Relevance
“…3B). A slightly higher apoptotic effect of PMA was observed in PKC-depleted LNCaP cells, consistent with its prosurvival effect in this model (McJilton et al, 2003;Meshki et al, 2010). Most importantly, only PKC␦ depletion could significantly impair TNF␣ release by the phorbol ester, whereas depletion of either PKC␣ or PKC failed to block secretion of the death factor (Fig.…”
Section: Methodssupporting
confidence: 63%
“…3B). A slightly higher apoptotic effect of PMA was observed in PKC-depleted LNCaP cells, consistent with its prosurvival effect in this model (McJilton et al, 2003;Meshki et al, 2010). Most importantly, only PKC␦ depletion could significantly impair TNF␣ release by the phorbol ester, whereas depletion of either PKC␣ or PKC failed to block secretion of the death factor (Fig.…”
Section: Methodssupporting
confidence: 63%
“…Expression of PKC⑀ was readily detected 24 h after infection and remained stable for several days (Ref. 24) and data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Studies from several laboratories, including ours, revealed that PKC␦ generally acts as a negative regulator of proliferation and/or mediates apoptotic responses, whereas PKC⑀ is a prosurvival and mitogenic kinase (19 -22). In prostate cancer cells, activation of PKC⑀ accelerates G 1 /S transition, mediates survival through Bad-dependent and Bad-independent mechanisms, and confers androgen independence (23)(24)(25). Most interestingly, PKC⑀ emerged as a potential oncogene and cancer biomarker and it is up-regulated not only in prostate cancer but also in several other epithelial cancers including lung, breast, and thyroid cancer (19,26,27).…”
mentioning
confidence: 99%
“…Furthermore, PKC -mediated antiapoptotic properties are obtained through the effects on multiple signaling pathways, such as phosphorylation and inactivation of proapoptotic Bad [444], inhibition of TNF -induced JNK activation [444], inhibition of I B phosphorylation and degradation [445], and interaction of PKC with proapoptotic Bax, all of which result in the neutralization of apoptotic signals [446]. Furthermore, PKC increases P-gp-mediated drug resistance [447].…”
Section: Prostate Cancermentioning
confidence: 99%